f(3)=2(3)(6)-4(3)

Simple and best practice solution for f(3)=2(3)(6)-4(3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for f(3)=2(3)(6)-4(3) equation:



f(3)=2(3)(6)-4(3)
We move all terms to the left:
f(3)-(2(3)(6)-4(3))=0
We add all the numbers together, and all the variables
f3-193=0
We add all the numbers together, and all the variables
f^3-193=0
We do not support efpression: f^3

See similar equations:

| 18x-9=4x+5 | | v+4/5=9/5 | | 4x-2x+7=-21 | | 4-10x=44 | | 11x+15=6x+70 | | 447+x=−261 | | 15+4h=3+6h | | -3-4n=1-6n | | 9+2m-5-3=5m-5 | | 192=44-x | | y/3=1/21 | | 46=5x+3(x+2) | | a÷-2+9=30 | | b/2-5=6 | | 5+5u=6u-4 | | 16j+18=-20-10+20j | | 2u-1=-9-2u | | 13b+19=12b | | 2x+18x-10=47 | | 6-2j=10 | | x+3,000=21,000 | | 2x+4=-4x+5 | | 1=13+r/9 | | 35x+55-10x+28x+75-5x+12=0 | | 16=-8(7+p) | | 12x-4=8x24 | | x=25+10-20 | | 25h=15h+75 | | 7u-47=3(u-9) | | 23x+34=23-12x7x | | -9-(-2)-(-5)=x | | 5y+40=6y-70 |

Equations solver categories